Hi there,
I'm having a problem with an equation in economics.
It goes like this: C= C(subscript 0) +cY (where Y =[C(subscript 0) +I=G]/(1-c)
So with substitution it goes:
C = C(0) + cY = C(0) + c[C(0) + I + G]/(1-c) = [C(0) +c(I+G)]/(1-c)
It's the last step I don't get where the C(0) leaves the bracket and the whole thing is then divided by (1-c)
Any hints appreciated!
I'm having a problem with an equation in economics.
It goes like this: C= C(subscript 0) +cY (where Y =[C(subscript 0) +I=G]/(1-c)
So with substitution it goes:
C = C(0) + cY = C(0) + c[C(0) + I + G]/(1-c) = [C(0) +c(I+G)]/(1-c)
It's the last step I don't get where the C(0) leaves the bracket and the whole thing is then divided by (1-c)
Any hints appreciated!